An ''integrative neuroscience'' perspective on ADHD: linking cognition, emotion, brain and genetic measures with implications for clinical support. (October 2010) - Williams, Leanne M; Tsang, Tracey W; Clarke, Simon; Kohn, Michael
There remains a translational gap between research findings and their implementation in clinical practice that applies to attention-deficit/hyperactivity disorder (ADHD), as well as to other major disorders of brain health in childhood, adolescence and adulthood. Research studies have identified potential ''markers'' to support diagnostic, functional assessment and treatment decisions, but there is little consensus about these markers. Of these potential markers, cognitive measures of thinking functions, such as sustaining attention and associated electrical brain activity, show promise in complementing the clinical management process. Emerging evidence highlights the relevance of emotional, as well as thinking, functions to ADHD. Here, we outline an integrative neuroscience framework for ADHD that offers one means to bring together cognitive measures of thinking functions with measures of emotion, and their brain and genetic correlates. Understanding these measures and the relationships between them is a first step towards the development of tools that will help to assess the heterogeneity of ADHD, and aid in tailoring treatment choices.